Kinetics of Natural Attenuation: Review of the Critical Chemical Conditions and Measurements at Bore Scale. (2002) - Atteia, O.; Franceschi, M.
Abstract : This paper describes the chemical conditions that should favour the biodegradation of organic pollutants. Thermodynamic considerations help to define the reaction that can occur under defined chemical conditions. The BTEX (benzene, toluene, ethylbenzene, and xylene) degradation is focused on benzene, as it is the most toxic oil component and also because it has the slowest degradation rate under most field conditions. Several studies on benzene degradation allow the understanding of the basic degradation mechanisms and their importance in field conditions. The use of models is needed to interpret field data when transport, retardation, and degradation occur. A detailed comparison of two existing models shows that the limits imposed by oxygen transport must be simulated precisely to reach correct plumes shapes and dimensions, and that first-order kinetic approaches may be misleading. This analysis led us to develop a technique to measure directly biodegradation in the field. The technique to recirculate water at the borehole scale and the CO2 analysis are depicted. First results of biodegradation show that this technique is able to easily detect the degradation of 1 mg/l of hydrocarbons and that, in oxic media, a fast degradation rate of mixed fuel is observed.